RELIGIOUS DEVELOPMENT OF FOSTERED CHILDREN IN TANGERANG CLASS I CHILDREN’S SPECIAL DEVELOPMENT INSTITUTION - Wahid, Hidayat Nur; Jarodi, Odi (Universitas Nusa Cendana, 2025)
This research examines religious development in the Tangerang Class I Children's Special Development Institution, which is important given the increase in law violations by children in Indonesia. Although the existing justice system regulates children's rights, challenges in the development of children in conflict with the law, especially in the religious aspect, still need to be addressed. The purpose of this study is to explore the implementation of religious guidance and its impact on the character development of fostered children. The method used is qualitative with a case study approach, where data is collected through interviews, observations, and document analysis involving foster children and correctional officers. The results showed that religious development Tangerang Class I Children's Special Development Institution focused on two religions, Islam and Christianity, and was implemented in a structured manner. The program has succeeded in improving the religious knowledge and positive character of the juveniles, which can be seen from improvements in worship and self-awareness. However, this study also identified various challenges in implementation that need to be addressed to achieve optimal results. Keywords : Religious Guidance; Child Prisoners; Behavioral Development